Analysis of the Influence of Promotions and Price Strategies on Competitive Advantage Moderated by E-Commerce - Alfian Saputra Iriawan; Alfiana (Optima Science, 2025)
The purpose of this study is to analyze the impact of promotion and pricing strategies on competitive advantage, and also e-commerce as a moderating variable. The population sample used in this study is consumers of Golden Hill by Golden Tulip Batu in the period October to December 2024, and the sample was taken using the Simple Random Sampling technique, with a total of 100 respondents. The data will then be processed using Smart Partial LeastSquare (PLS) software. The results of this study indicate that better promotion can increase competitive advantage, as well as the right pricing strategy can increase competitive advantage. It was also found in this study that E-commerce has a strong moderating role in the relationship between promotion and competitive advantage. And e-commerce also has a strong moderating role in the relationship between pricing strategy and competitive advantage at Golden Hill by Golden Tulip Batu.